1988
DOI: 10.1172/jci113414
|View full text |Cite
|
Sign up to set email alerts
|

Is atriopeptin a physiological or pathophysiological substance? Studies in the autoimmune rat.

Abstract: Atriopeptin (AP), a natriuretic-diuretic and vasodilatory peptide, is synthesized and secreted from mammalian atria. The definitive role of this peptide on cardiovascular physiology and pathophysiology has yet to be determined. We developed a population of autoimmune rats sensitized against their own AP to evaluate the consequences of prolonged AP deficiency on physiological and pathophysiological processes. Natriuresis in response to acute intravenous volume expansion was inhibited in the autoimmune rat, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Most importantly, by mimicking endogenous levels of elevated ANF by infusion of exogenous ANF in the thoracic inferior vena caval dogs, we can differentiate between the contribution of atrial stretch and activation of neurogenic reflexes as compared to ANF in mediating the maintenance of sodium excretion and possible suppression of activation of the RAAS in acute CHF. Indeed, these studies are consistent with the recent studies of Greenwald and colleagues (25), who have demonstrated a role for ANF as an acute regulator of intravascular volume during states of acute volume overload. Caution should be exercised regarding the complexity of various opposing vasoactive and sodium regulating systems operative in CHF; yet, the studies support a contributing homeostatic role for endogenous ANF in acute CHF.…”
Section: Methods Ofmeasurementsupporting
confidence: 91%
“…Most importantly, by mimicking endogenous levels of elevated ANF by infusion of exogenous ANF in the thoracic inferior vena caval dogs, we can differentiate between the contribution of atrial stretch and activation of neurogenic reflexes as compared to ANF in mediating the maintenance of sodium excretion and possible suppression of activation of the RAAS in acute CHF. Indeed, these studies are consistent with the recent studies of Greenwald and colleagues (25), who have demonstrated a role for ANF as an acute regulator of intravascular volume during states of acute volume overload. Caution should be exercised regarding the complexity of various opposing vasoactive and sodium regulating systems operative in CHF; yet, the studies support a contributing homeostatic role for endogenous ANF in acute CHF.…”
Section: Methods Ofmeasurementsupporting
confidence: 91%
“…After the submission of our manuscript, Needleman's group reported the effect of autoimmunization with ANP in SHR on the development of hypertension (50). They failed to detect any alteration in the increase of blood pressure of autoimmune SHR sensitized against ANP, compared with nonimmune SHR.…”
Section: Discussionmentioning
confidence: 92%
“…Attempts to confirm a participatory role of ANF in the mineralocorticoid escape phenomenon using passive immunization with anti-ANF antiserum have produced conflicting results (22,33). However, recently, Morishita et al (34) isolated the natriuretic peptide receptor antagonist HS-142-1 (HS) from a culture broth of Aureobasidium pullulans melangimum var.…”
Section: Introductionmentioning
confidence: 99%